Echocardiographic assessment of felines sedated with dexmedetomidine or xylazine associated with butorphanol (Research, Society and Development, 2022)
This prospective cohort study aimed to evaluate by echocardiogram the cardiovascular effects of α2 agents associated with butorphanol in cats. A group of 18 mixed-breed cats with a mean weight of 3.65 + 0.7 kg, with an approximate age of 6 months. The cats were assigned in three groups, XB (Xylazine/butorphanol group) sedation with 0.5 mg/kg of xylazine and 0.5 mg/kg of butorphanol IM; DB (Dexmedetomidine/butorphanol group): sedation with 20 µg/kg of dexmedetomidine and 0.5 mg/kg of butorphanol IM; C: control group which received saline solution in volume approximated to those used in the other groups, IM. Echocardiographic variables as ejection fraction (Simpson's method and M-mode) and left ventricular shortening fraction (M-mode), ejection volume, end-systolic volume and cardiac output (Teichholz), tissue Doppler E' and A' wave velocities and cardiac index were evaluated. There was a reduction in echocardiographic variables compared with the control group, being statistically significant for heart rate, ejection fraction (% by Simpson), shortening fraction (% in M-mode) and end-systolic volume in XB and DB groups, and tissue Doppler E' and A' wave velocity (m/s), E'/A' ratio, cardiac output and cardiac index only in XB group. When compared to each other, XB and DB differed significantly in the tissue Doppler E' and A' wave velocity (m/s), and E'/A' ratio. Xylazine was more deleterious than dexmedetomidine in most of the variables evaluated, leading to a significant reduction in cardiac output and cardiac index at the doses used in this study.